2019
DOI: 10.3389/fpubh.2019.00393
|View full text |Cite
|
Sign up to set email alerts
|

Social Mechanisms in Epidemiological Publications on Small-Area Health Inequalities—A Scoping Review

Abstract: Background: Small-area social mechanisms-social processes involving the social environment around the place of residence-may be playing a role in the production of health inequalities. Understanding how small-area health inequalities (social environment affects health and consequently contribute to inequalities between areas) are generated and the role of social mechanisms in this process may help defining interventions to reduce inequalities. In mediation and pathway analyses, social mechanisms need to be tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…But while some social mechanisms can be operationalised as attributes of a neighbourhood via individual perception (social cohesion), others are processes (social contagion) and more difficult to operationalise in order to be studied within the framework of regression analysis. 7 Accordingly, in a recent literature review, we could not identify any studies with a focus on the effect of social contagion as a mechanism in the production of small-area health inequalities. 7 However, some evidence on the role of social contagion in a small-area context has been established.…”
Section: What This Study Addsmentioning
confidence: 97%
See 1 more Smart Citation
“…But while some social mechanisms can be operationalised as attributes of a neighbourhood via individual perception (social cohesion), others are processes (social contagion) and more difficult to operationalise in order to be studied within the framework of regression analysis. 7 Accordingly, in a recent literature review, we could not identify any studies with a focus on the effect of social contagion as a mechanism in the production of small-area health inequalities. 7 However, some evidence on the role of social contagion in a small-area context has been established.…”
Section: What This Study Addsmentioning
confidence: 97%
“…7 Accordingly, in a recent literature review, we could not identify any studies with a focus on the effect of social contagion as a mechanism in the production of small-area health inequalities. 7 However, some evidence on the role of social contagion in a small-area context has been established. For example, Hedström et al showed how social contagion occurs in social networks with political interests.…”
Section: What This Study Addsmentioning
confidence: 97%
“…The strategy was informed by previous reviews conducted among Black communities, [32][33][34][35][36][37] on mental health and psychosis [38][39][40][41] as well as on health inequalities more generally. [42][43][44] In addition, search lines relating to Canada and its provinces and territories were devised and used in combination with the three concepts mentioned. The final search strategy included relevant subject headings and keywords.…”
Section: Studies Identificationmentioning
confidence: 99%
“…Strategies from previous reviews were reviewed to inform and design the search used in this review. Reviews on Black individuals and communities [23][24][25] on cancer [26][27][28] and health inequalities [29][30][31] were considered. The final search strategy included relevant subject headings and keywords and was executed on December 15, 2021.…”
Section: Identification Of Studiesmentioning
confidence: 99%